Testing the Relationship Between Entrepreneurial Intention and its Antecedents on University Students Using PLS-SEM - Shandilya, Saptadweepa (Prabandhan: Indian Journal of Management, 2022)
The concept of entrepreneurial intention serves as an emerging area of interest for researchers due to its close association with psychological models and theories. One of the leading theories in this field is the theory of planned behavior (TPB) (Ajzen, 1991), which considers the social and cultural environment affecting human behavior. Taking cues from the theory, the relationships between entrepreneurial intention and its three antecedents, that is, attitude towards the behavior (personal attitude), subjective norms, and perceived behavioral control, were tested in this paper. Students pursuing post-graduation in business and commerce stream across several universities in Kamrup (Metro) district of the state of Assam were considered as the sample for this study. To test the hypotheses, partial least squares structural equation modeling (PLS-SEM) was carried out using SmartPLS Version 3.3.3. The results confirmed the existence of significant relationships between the four constructs of TPB. It also revealed the existence of partial mediation across the several paths of the research model. As such, the study validated the applicability of the TPB on the said sample. Moreover, the moderating effect of gender as a categorical variable was tested for the sample. The results from the multi-group analysis showed that gender exerted no significant influence on the relationship between EI and its three antecedents.